A proposed career guidance program and a predictive validity study of the NCEE for La Salette College - Bautista, Imelda Brillantes (Animo Repository, 1975)
This first part of this study proposes a career guidance program for La Salette College of Santiago, Isabela. The descriptive normative survey method was used in this study. A survey was conducted among 117 freshmen, 129 sophomore students, and 13 faculty members at La Salette College. The questionnaire for the students and the faculty were both adapted from career counseling books, unpublished theses, and guidance monographs. The questions were revised and adapted to suit local needs. Results of the survey pointed to a need for a Career Guidance Program because the students needed help in assessing their abilities and interests. Twenty-nine percent of the total sample took preparatory courses and would need help later on to chart out their careers. Also, twenty-six percent of the total population took courses which were not of their own choice. The problems which were enumerated by the students included career decisions, financial problems, difficulty in coping with their subjects, uncertainty of future employment, lack of knowledge about the course enrolled in, and lack of knowledge about job opportunities. The second part of the study aims to find out the validity and usefulness of the students' NCEE results and High School Grade Average for the prediction of freshman college success. The study included 27 commerce and 18 pre-nursing freshmen of the La Salette College in the first semester of 1974-1975. The NCEE results, high school grade average (HSGA), and college grade average (CGA) were the variables used for the validity and prediction study. The data, all in T-scores, were treated in three ways : simple correlation, multiple correlation, and regression equation. Results of the study showed that there was a significant relationship between the CGA and the NCEE results. Also, there was a significant relationship, at the .01 level, between the CGA, NCEE results, and HSGA combined for both the AA-PN and the BSBA groups. The NCEE results and the HSGA both validly contributed to the prediction of the criterion variable (CGA).